Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China - Qian, Yu-Han; Du, Yu-Zhou (Zootaxa, 2013)
Two new species of the leuctrid genus Rhopalopsole from China are described, R. curvispina Qian & Du, sp. nov. and R. triseriata Qian & Du, sp. nov. The new species are compared to similar species in R. dentata group and R. magnicercia group.